Xenograft recipients and the right to withdraw from a clinical trial - Bobier, Christopher; Hurst, Daniel J.; Rodger, Daniel; Omelianchuk, Adam (Bioethics, 2024)
Preclinical xenotransplantation research using genetically engineered pigs has begun to show some promising results and could one day offer a scalable means of addressing organ shortage. While it is a fundamental tenet of ethical human subject research that participants have a right to withdraw from research once enrolled, several scholars have argued that the right to withdraw from xenotransplant research should be suspended because of the public health risks posed by xenozoonotic transmission. Here, we present a comprehensive critical evaluation of the claim that xenotransplant recipients should be required to waive their right to withdraw from lifelong biosurveillance. We conclude that if xenotransplantation requires participants to waive their right to withdraw, then clinical trials may not be justifiable, given the ethical and legal obstacles involved with doing so. Consequently, if clinical trials are permitted with a right to withdraw, then they may pose a significant public health risk.